Comparative sensitivity of automated (Abbott M2000) and manual plasma HIV-1 RNA PCR assays for the detection of persistent viremia after long-term antiretroviral therapy - Melissa A. Tosiano; Hanna Mar; Dianna Hoeth; Joseph J. Eron; Rajesh T. Gandhi; Deborah K. McMahon; Ronald J. Bosch; John W. Mellors; Joshua C. Cyktor (Elsevier, 2022)
Background: The ability of automated, FDA-cleared plasma HIV-1 RNA assays to detect low-level viremia, compared to manual, highly sensitive research-only methods, is not well-defined. We therefore tested paired plasma samples from people with HIV-1 (PWH) on long-term antiretroviral therapy (ART) with both the Abbott M2000 RealTime HIV-1 Viral Load assay (Abbott) and a quantitative reverse transcriptase (RT)-initiated PCR assay that has a reported 95% detection limit of 1 HIV-1 RNA copy/ml (single copy assay, SCA). Methods: Plasma samples from 309 participants in the AIDS Clinical Trials Group study A5321 were tested by both Abbott and SCA. Participants were mostly men (82%). All were on stable ART for a median of 7 years with HIV-1 RNA <40 copies/mL by Abbott. Pooled plasma from each donor was divided and tested. Abbott results were reported as target detected <40 copies/mL but not quantifiable (target detected <40) or target not detected (TND), and SCA results were classified as HIV-1 RNA detected or not detected. Results: By Abbott, 17% (51/309) of sample results were target detected <40, whereas 83% (258/309) were TND. Of the samples that were target detected <40 by Abbott, 73% (37/51) had HIV-1 RNA detected by SCA. By contrast, 43% of samples that were TND by Abbott (110/258) had HIV-1 RNA detected by SCA (p < 0.001). Conclusion: Plasma samples from PWH with HIV-1 RNA detected but <40 copies/ml by the automated Abbott M2000 assay are likely (73% of 51 samples) to have HIV-1 RNA detected by an optimized manual assay with single copy sensitivity. An Abbott HIV-1 RNA result of target not detected did not exclude low-level viremia: 43% of 258 samples had HIV-1 RNA detected by the single copy assay. These findings indicate that the Abbott M2000 assay cannot exclude the persistence of viremia on ART and thus may have less utility, compared to a manual single copy assay, for assessing the impact of experimental interventions designed to eliminate low-level viremia as a step towards achieving ART-free HIV-1 remission.